Penerapan Metode Joyfull Learning Berbasis Ice Breaking Untuk Meningkatkan Minat Belajar Bahasa Arab Pada Siswa di Kelas VIII MTS Negeri 1 Wonosobo Tahun Ajaran 2022/2023 - Jevi Irviana; Chairani Astina; Muhammad Saefullah (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The aim of this study: 1) To find out how this ice-breaking-based joyfull learning method is applied to grade VIII MTs Negeri 1 Wonosobo students, 2) To assess whether interest in learning Arabic has increased among grade VIII students of MTS Negeri 1 Wonosobo, 3) The class is divided into two parts: experimental class and control class.This research is motivated to increase the interest of grade VIII students of MTS Negeri 1 Wonosobo. Teachers have an important task, namely using the right method, namely the ice-breaking-based joyfull learning method. This study used an experimental quantitative approach with pre-test and post-test. Data collection is carried out through observation, interviews, documentation, tests, and questionnaires. And to analyze the data researchers derive from conclusions. Then for the results of this study it was shown that; 1) joyfull learning method that uses an ice breaking approach applied to class VIII MTs Negeri 1 Wonosobo is quite effective. 2) The interest in learning Arabic in students in class VIII MTs Negeri 1 Wonosobo is good and increasing. 3) There is a comparison of the results of the two classes available, namely the experimental class and the control class, from the two classes the experimental class found an increase in interest in learning Arabic. It can be concluded that the joyfull learning method based on the ice breaking approach can increase the interest of grade VIII students in learning Arabic MTs Negeri 1 Wonosobo.